Dental Sinus Infections- Why are we Still Missing the Well Documented Diagnosis? - Florian, Bast; Priyanka, Chadha; James, Shelley; Jonathan, Collier (Journal of Otolaryngology Advances, 2017)
Background: Dental infections, salivary gland lesions, neoplasms and developmental abnormalities can cause oral cutaneous fistulae, fistulae of the neck and intraoral fistulae. Published case reports deliver the same message; that these lesions are misdiagnosed and treated late and ineffectively and this remains a significant on-going problem. Aim: It is important to reiterate the management and diagnosis of this condition, despite the fact that it is already well documented in the current literature as patients are still being subjected to unnecessary treatment. Design and Setting: We performed a retrospective review of 5 consecutive dental sinus infections between June 2013 and January 2014 that were misdiagnosed initially. Information was extracted from the medical case notes of 2 male and 3 female patients with an age range from 12-87 years. Method: The medical records of all 5 patients were analyzed, medical photography was taken and the patients were followed up regularly in our clinic. Results: Each patient presented with a non-healing lesion and all were treated with either oral or topical antibiotics. Patients were eventually referred to the craniofacial department where they all received an orthopantomogram and underwent dental extraction, which led to complete healing. Conclusion: Cutaneous facial sinus tracts of odontogenic origin are often initially misdiagnosed which leads to prolonged and inappropriate treatment. Correct diagnosis and treatment will result in predictable and rapid healing and thus it is essential to record these case series, to ensure that medical professionals are aware of the presenting symptoms, which can often be very subtle.
Keywords: Dental sinus; treatment; odontogentic; tooth extraction; antibiotics